Pengembangan Media Pembelajaran Berbasis Blended Learning pada Mata Kuliah Sejarah Indonesia Kontemporer Program Studi Pendidikan Sejarah Universitas Batanghari Jambi - Nur Agustiningsih; Nurul Fitri (Jurnal Ilmiah Dikdaya, 2020)
The purpose of this research is to find out (1) the process of learning media development based blended learning for Indonesia Contemporary History subject of History Education Program batanghari University Jambi, (2) The eligibility of learning media based blended learning for Indonesia Contemporary History subject of History Education Program Batanghari University Jambi. The types of this research are research and development. This research emphasizes an effort to produce certain products that will be used in certain fields of science and can also be used in an activity that needs it. The development which was carried out in this research is developing of learning media based on blended learning in the form of an ebook. To determine the feasibility of the media, the media experts and material experts validated the media that had been made and then conducted a media trial to the students, the trial was carried out on three stages, one to one, small group trials, and field test trials. The results showed that (1) the stages of developing blended learning based media in Indonesia Contemporary History subject adopted the steps or stages which were developed by ADDIE which consisted of five stages, they are:  analysis, design, development, implementation, and evaluation. (2) The results of the assessment by media experts for all aspects obtained an average score of 4.25 with very good category and reasonable to be used. Furthermore, based on the media expert's assessment, the average of all aspects is 4.35 dan 4,48 after revision with a very good category so that the material reasonable to be used. The advisability of blended learning based media in Indonesia Contemporary based on student assessment in the field test obtained an average of all aspects 4.45 in the very good category so that the media was very suitable to be used in this learning activity.